Measurements and modeling of cold 13CH4 spectra in the 3750–4700 cm−1 region. (May 2016) - Brown, L.R.; Nikitin, A.V.; Sung, K.; Rey, M.; Tashkun, S.A.; Tyuterev, Vl.G.; Crawford, T.J.; Smith, M.A.H.; Mantz, A.W.
Abstract: A new study of 13 CH4 line intensities and positions was performed in the Octad region between 3750 and 4700 cm −1 . Using 13 C-enriched samples, spectra were recorded with both the McMath–Pierce FTS at Kitt Peak Observatory in Arizona and the Bruker IFS-125HR at JPL. Sample temperatures ranged between 80 and 296 K. Line positions and intensities of 15, 000 features were retrieved at different temperatures by non-linear least squares curve-fitting procedures. Intensities were used to estimate the lower state energies for 60% of the features in order to determine quantum assignments up to J =10. A preliminary analysis was performed using the effective Hamiltonian and the effective dipole transition moment expressed in terms of irreducible tensor operators adapted to spherical top molecules. Selected assignments were made up to J =10 for all 24 sub-vibrational states of the Octad; these were modeled for 4752 experimental line positions and 3301 selected line intensities fitted with RMS standard deviations of 0.004 cm −1 and 6.9%, respectively. Integrated intensities of the eight Octad bands are compared to ab initio variational calculations. A prediction of the 13 CH4 is given, but further analysis to improve the calculation will be reported in the future. Highlights: 15, 000 13 CH4 line positions and intensities were measured from 3750 to 4700 cm −1 . Empirical lower state energies were derived from cold spectra (225 to 80 K). Transitions reaching 24 vibrational sub-states of the 13 CH4 Octad were assigned. 4752 line positions (and 3301 intensities) were modeled to 0.004 cm −1 (and 7.0%). Integrated intensities agree with ab initio variational calculations within 0.3%.